2022
DOI: 10.1111/eva.13443
|View full text |Cite
|
Sign up to set email alerts
|

Urban rendezvous along the seashore: Ports as Darwinian field labs for studying marine evolution in the Anthropocene

Abstract: Humans have built ports on all the coasts of the world, allowing people to travel, exploit the sea, and develop trade. The proliferation of these artificial habitats and the associated maritime traffic are not predicted to fade in the coming decades. Ports share common characteristics: species find themselves in novel singular environments, with particular abiotic properties -e.g., pollutants, shading, protection from wave action-within novel communities in a melting-pot of invasive and native taxa. Here we di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 191 publications
0
16
0
Order By: Relevance
“…Pervasive introgression implies that most co-occurring introduced and native genomes of sister species are still to some extent permeable to interspecific gene flow, with various outcomes from genome-wide genetic swamping to adaptive introgression at few specific genomic regions (McFarlane and Pemberton 2019). In the marine realm, harbors, docks and piers are prime locations for such hybridization events between non-native and native lineages, sometimes resulting in singular outcomes (Touchard et al 2022). For example, Simon et al (2020) identified a unique ecotype of marine mussels in these artificial habitats ("docks mussels"), resulting from a recent admixture between two closely-related European mussel species.…”
Section: Introductionmentioning
confidence: 99%
“…Pervasive introgression implies that most co-occurring introduced and native genomes of sister species are still to some extent permeable to interspecific gene flow, with various outcomes from genome-wide genetic swamping to adaptive introgression at few specific genomic regions (McFarlane and Pemberton 2019). In the marine realm, harbors, docks and piers are prime locations for such hybridization events between non-native and native lineages, sometimes resulting in singular outcomes (Touchard et al 2022). For example, Simon et al (2020) identified a unique ecotype of marine mussels in these artificial habitats ("docks mussels"), resulting from a recent admixture between two closely-related European mussel species.…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue, dispersal across the seascape and consequences for management are studied in multiple systems, including microalgae, corals, mollusks, and fish. Touchard et al ( 2022 ) address marine evolution and local adaptation in ports and other areas, which are strongly impacted or rapidly changed by human activities. The authors discuss how rapid evolution in harbors, for instance, driven by adaptation to toxins or hybridizations, has been accelerated by a combination of human impacts, the mixing of native and invasive taxa, and elevated connectivity over large spatial distances due to boating activities.…”
Section: Overview Of the Issuementioning
confidence: 99%
“…The responses of populations to future climate change (in terms of adaptive capability, range shifts, and expansions of native and nonnative/invasive species) depend, in part, on individuals' dispersal abilities across the seascape (realized connectivity/gene flow). In this Special Issue, dispersal across the seascape and consequences for management are studied in multiple systems, including microalgae, corals, mollusks, and fish Touchard et al (2022). address marine evolution and local adaptation in ports and other areas, which are strongly impacted or rapidly changed by human activities.…”
mentioning
confidence: 99%
“…Anthropogenic transport of species facilitates secondary contact between previously isolated species or lineages by altering connectivity pathways and acting as corridors and stepping stones (Airoldi et al, 2015; Alter et al, 2020; Bishop et al, 2017). These secondary contacts can result in anthropogenic hybridisations between native and non-indigenous species or lineages, and, as are post-glacial hybrid zones (Hewitt, 1988), they represent life-size evolutionary experiments for the study of the mechanisms and consequences of hybridisation (Touchard et al, 2022; Viard et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It could suggest the initial introgression quickly spread to the other regions thanks to shipping activities connecting these areas. Mosaic distributions are indeed often observed in the case of human-mediated dispersal via shipping (Touchard et al 2022). In addition, the observed pattern is concordant with the one reported for neutral markers in European populations of C. intestinalis (Hudson et al, 2016 ;Le Moan et al, 2021).…”
mentioning
confidence: 99%